LEGALISASI ARSIP ELEKTRONIK SEBAGAI ALAT BUKTI HUKUM: Array - Rusmiatiningsih Rusmiatiningsih (Jurnal Kearsipan, 2017)
The information packaging from manual to digital form is a trend of the feature of information arising from the information technology development. In general, the scope of archives management in Indonesia includes some troubles on information packaging, for example, the case of the legality on electronic archives, and the notion that all people can manage the archival works without having any specific expertise and knowledge. Thus, nowadays, it is quite difficult to find professional archivists. Having seen the situation, this research tries to discuss on the interpretation or description on two main problems, namely, the position of electronic archives as legal evidences which are still doubted in the court, and the archivists’ roles as both records and archives managers and expert witness in the court. This is a descriptive and qualitative research with a literature approach. The research concludes that 1. Electronic archives are eligible to be used as the legal evidences in the court. 2. It is important to position archivists not only as the person in charge of the records and archives management but also as the witness expert in court because they have good competency to solve the legal evidence problems in the court. Kemasan informasi dari manual menjadi bentuk digital merupakan sebuah tren bentuk informasi yang ditimbulkan dari perkembangan teknologi informasi. Dalam lingkup pengelolaan arsip secara profesional di Indonesia, terdapat beragam kendala mengenai arsip dalam kemasan digital, antara lain: kasus legalisasi arsip elektronik, serta anggapan bahwa pengelolaan arsip adalah pekerjaan sepele yang hanya bertugas menyimpan arsip sehingga menyebabkan langkanya tenaga arsiparis profesional. Merujuk pada kenyataan tersebut, maka tulisan ini mencoba untuk memberikan interpretasi atau gambaran terhadap dua pokok permasalahan, yakni; pertama, posisi arsip elektronik sebagai alat bukti hukum yang masih dianggap diragukan; kedua, peran arsiparis dalam lingkup hukum. Penelitian ini menggunakan metode kualitatif deskripsif dengan pendekatan studi literatur. Dari hasil pembahasan ditemukan bahwa 1. Posisi arsip elektronik adalah memiliki legalitas yang sah sebagai alat bukti hukum dalam kasus persidangan, 2. Peran arsiparis bukan hanya mengelola arsip dinamis dan statis, tetapi juga dalam ruang lingkup hukum arsiparis sangat berperan vital sebagai saksi ahli yang memiliki kompetensi dalam memecahkan alat bukti hukum.